A Comparative Study between Extroverted and Introverted Students and Their Speaking Ability - Eva Nurmayasari; Silvia Rahmawati (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2014)
Speaking is one of abilities in English learning which is required to communicate one another. Some students usually get the difficulties to speak. On the other hand some other students are active in speaking in their classroom. One of causes of those problems relates to the personality. Based on dimensions of attitude, there are two types of personalities, such as extrovert and introvert personality. This study is limited to find out the comparison between extroverted and introverted students in their speaking ability. This comparative research uses quantitative method; therefore t-test. Questionnaire is used to classify who has extrovert and introvert personality. To measure the speaking ability, this research uses speaking score of speaking in professional context II and speaking for academic purposes. The correct formula of t-test can be chosen toward F-test. The total of two uncorrelated samples are not same, but homogenous, thus this research uses polled variance of t-test formula. From this research, the t-test shows that t-observed is 0,72, while the t-table which ? 5% is 2,021. t-table is higher than t-observed. This result proves that Ho is accepted; there is no difference between extroverted and introverted students toward their speaking ability. It means, there are not any better students in speaking between both extroverted and introverted students.